Sexual Risk Behavior and its Impact on Unwanted Pregnancy Among Adolescents - Fenny Etrawati; Yeni Yeni; Widya Lionita; Annisa Rahmawaty; Desy Nuri Fajarningtiyas (Jurnal Ilmu Kesehatan Masyarakat, 2023)
Sexual activity among adolescents is increasingly alarming; the results of a national survey identified about 4.5% of teenage boys and 0.7% of teenage girls have had sexual intercourse that triggers unwanted pregnancies. This study analyzed the influence of risky sexual behavior factors in adolescents on the incidence of unwanted pregnancy. This research is a secondary data analysis sourced from Indonesian Demographic and Health Survey (IDHS) data in 2017 using a cross-sectional design. The study sampled 15-24-year-olds who had sexual intercourse with as many as 1532 people. Data were analyzed univariately while  bivariate analysis using Chi-Square test and multivariate analysis with logistic regression test of the risk factor model. The results showed unwanted pregnancy occurred in 8.6% of adolescents who had a history of having sexual intercourse. In addition, it will be 4.5 times greater risk of unwanted pregnancy occurred in adolescents who performed risky behaviors such as fingering and stimulating each other after being controlled by variable confounding age and age when first having sex (PR = 4.570). Therefore, equal access to reproductive health education is needed both in educational institutions and in the community as an effort to prevent unwanted pregnancy.